2021
DOI: 10.1093/rheumatology/keaa921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on phenotype and prognosis in IgA vasculitis

Abstract: Objectives Immunoglobulin A vasculitis (IgAV) is a small-vessel vasculitis most frequently benign in children while more severe in adults. We aimed to study the impact of age on presentation and outcome of adult IgAV. Methods We conducted a nationwide retrospective study including 260 IgAV patients. Patients were divided into four quartiles according to the age at IgAV diagnosis: <36, 36 ≤ age < 52; 52 ≤ age &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…IgAV. 45,48 ESRD, End-stage renal disease; IgAV, IgA vasculitis; IgAV-N, IgA vasculitis nephropathy.…”
Section: Increased Mortality In Older Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…IgAV. 45,48 ESRD, End-stage renal disease; IgAV, IgA vasculitis; IgAV-N, IgA vasculitis nephropathy.…”
Section: Increased Mortality In Older Patients Withmentioning
confidence: 99%
“…IgAV-associated joint involvement in adults has been reported in 30% to 60% of cases. 44,45 It is transient, migratory, and overall nondestructive. 20,21 The knees and ankles are the most commonly affected joints.…”
Section: Jaad Intmentioning
confidence: 99%
“…IgA vasculitis is more severe in adults. While joint and gastrointestinal involvement is more common in younger patients, severe purpura and glomerulonephritis are more common in older patients ( 15 ). IgA vasculitis is the most common vasculitis of childhood.…”
Section: Stepwise Algorithmic Approach In the Diagnosis Of Cutaneous ...mentioning
confidence: 99%
“…In addition, recent studies have shown that patients with tubular or interstitial lesions and glomerulosclerosis are associated with poor renal outcomes, and patients with both nephritic and nephrotic syndrome have the highest risk for progression to ESRD ( 6 9 ). Adult patients face a poorer prognosis than children, leaning more towards a protracted and chronic course, of who the incidence of ESRD is up to 32% ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%